SOCIO-ECONOMIC FACTORS INFLUENCING PASTORALISTS SEDENTARY/NOMADIC SETTLEMENT PATTERNS IN NASARAWA STATE, NIGERIA - A. A, GIREI; U, HARUNA; Y, and ADAMU (IJRDO-Journal of Agriculture and Research (ISSN: 2455-7668), 2017)
The study examined the socio-economic factors influencing pastoralist nomadic orsedentary settlement pattern in Nasarawa State, Nigeria. The specific objectives were todescribe the socio-economic characteristics of pastoralists, analyse socio-economicfactors influencing pastoralists’ nomadic / sedentary settlement pattern in the study areaand identify the common diseases / pest and prevention methods adopted by therespondent. A survey design was adopted for the study. A preliminary survey wasconducted in the Area to identify the major water points where pastoralists are found. Ineach Local District, one water point was randomly selected. Thirty percent (30%) of thesampling frame of nomadic pastorialist compile during the preliminary survey whereand used for the study. Primary data were collected with the aid of structuredquestionnaire. Descriptive (mean, frequency and percentages) and inferential (Logitregression) statistics to achieve the research objectives. The study revealed that all(100%) of the respondents were male, majority (74.4%) were married with meanhousehold size of5.83 persons, majority (67.8%) were living a sedentary life, the averageyears of experience of the respondents was estimated at 23.44 years, the mean number ofcattle, sheep and goat owned by the respondents were estimated at 168.60, 57.86 and31.28 respectively while the mean annual income of the respondents was estimated atN294,388.89. Logistic regression analysis revealed an R2 value of 0.246 and F-value of96.114. The study revealed that years of experience, household size and marital statussignificantly influenced system of living of the nomadic pastoralists in the study areaMajority (97.8%) indicated Foot and Mouth Disease (FMD) as a major disease affectingtheir livestock and all the respondents utilized the natural grassland. The studyrecommended that rangeland should be made available and accessible to nomadicpastoralists in the study area. Also, government and NGOs should design environmentalinitiatives that will address the issues of pest and disease in the study area and ensure afriendly environment that will support pastoralist activities